Development of Ego‐resiliency: Relations to Observed Parenting and Polymorphisms in the Serotonin Transporter Gene During Early Childhood. Issue 3 (24th July 2013) - Taylor, Zoe E.; Sulik, Michael J.; Eisenberg, Nancy; Spinrad, Tracy L.; Silva, Kassondra M.; Lemery‐Chalfant, Kathryn; Stover, Daryn A.; Verrelli, Brian C.
Abstract We used observed parenting behaviors, along with genetic variants and haplotypes of the serotonin transporter gene (SLC6A4), as predictors of children's ego‐resiliency during early childhood (N = 153). The quality of mothers' parenting was observed at 18 months of age, and mothers' reports of ego‐resiliency were collected at six time points from 18 to 84 months. Genetic data were collected at 72 months. Observed parenting was positively associated with initial levels of children's ego‐resiliency. Furthermore, although individual genetic variants of the serotonin transporter gene (LPR, STin2) were not associated with ego‐resiliency, the S10 haplotype (that combines information from these two variants) was negatively associated with initial levels of ego‐resiliency. Both parenting and serotonin genetic variation uniquely predicted children's ego‐resiliency, suggesting an additive effect of genetic and parental factors.